2014
DOI: 10.1021/ol502208w
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective N-Sulfonylaminoalkenylation of Azulenes from Terminal Alkynes and Azides via N-Sulfonyl-1,2,3-triazoles

Abstract: The development of rhodium-catalyzed diastereoselective N-sulfonylaminoalkenylation of azulenes using N-sulfonyltriazoles is described. This procedure can be successfully applied to rhodium-catalyzed diastereoselective N-sulfonylaminoalkenylation of azulenes starting from terminal alkynes and N-sulfonylazides via a three-component semi-one-pot process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…They have been used for the preparation of different types of heterocycles, N-sulfonyl-containing compounds, [27] and for stereoselectives ynthesiso f2 ,2-diaryl or 2-alkyl-2-aryl-substituted N-sulfonyl enamides ( Figure 1B). [28][29][30][31][32][33] We have recently shown that N-fluoroalkyl triazoles prepared by a[ 3 + +2] cycloaddition of stable and safe azido(per)fluoroalkanes anda lkynes [34][35][36] are efficiently transformed to new N-fluoroalkyl heterocycles via rhodiumc arbenoids. [37,38] However,t he reactivity profiles of Nfluoroalkyl triazoles and N-sulfonyl triazoles are markedlyd ifferent.…”
mentioning
confidence: 99%
“…They have been used for the preparation of different types of heterocycles, N-sulfonyl-containing compounds, [27] and for stereoselectives ynthesiso f2 ,2-diaryl or 2-alkyl-2-aryl-substituted N-sulfonyl enamides ( Figure 1B). [28][29][30][31][32][33] We have recently shown that N-fluoroalkyl triazoles prepared by a[ 3 + +2] cycloaddition of stable and safe azido(per)fluoroalkanes anda lkynes [34][35][36] are efficiently transformed to new N-fluoroalkyl heterocycles via rhodiumc arbenoids. [37,38] However,t he reactivity profiles of Nfluoroalkyl triazoles and N-sulfonyl triazoles are markedlyd ifferent.…”
mentioning
confidence: 99%
“…[26] Various substituted triazoles were tolerated in this reaction, although the 4-alkyls ubstituted triazole gave the desired product only in low yield. [26] Various substituted triazoles were tolerated in this reaction, although the 4-alkyls ubstituted triazole gave the desired product only in low yield.…”
Section: Attack By Carbon Atommentioning
confidence: 96%
“…Lee and co-workersr ecently reportedarhodium-catalyzed diastereoselective N-sulfonylaminoalkenylation of azulenes (Scheme 16). [26] Various substituted triazoles were tolerated in this reaction, although the 4-alkyls ubstituted triazole gave the desired product only in low yield. When unsubstituted azulene 77 was used as the reactant, products 79 were obtained as am ixture of Z and E isomers, whereas when alkylated azulene 78 was used, the products 80 were all obtained as the Z isomers.…”
Section: Scheme9synthesis Of 34-fused Indolesmentioning
confidence: 96%
“…This further rearranges itself to intermediate 9 which is sufficiently basic to abstract proton to regain aromaticity leading to stereoselective formation of C3 N-sulfonylamine alkenyl derivative indolizine. [17] In conclusion, we have disclosed an excellent methodology for highly stereoselective synthesis of C3 substituted N-sulfonylamine alkenyl derivatives of indolizines through rhodium(II) catalyzed insertion of azavinyl carbenes. Similaraly pyrrolo [1,2a]quinolines also reacts under optimal reaction condition to give their C1 N-sulfonylamine alkenyl derivatives.…”
mentioning
confidence: 92%
“…[16] Lee and coworkers reported diastereoselective CÀ H functionalization of non-benzenoid aromatic azulene moiety through aza-vinyl carbene insertion (Scheme 1b). [17] Similarly, numerous reports are available for CÀ H functionalization of heteroaromatics like indoles and pyrroles by AVC (scheme1c). [18] Recently, C3 selective CÀ H insertion of aza-vinyl carbenoids to carbazoles have been reported by Yoo and coworkers.…”
mentioning
confidence: 99%